Comparison of Transcriptional Changes to Chloroplast and Mitochondrial Perturbations Reveals Common and Specific Responses in Arabidopsis - Van Aken, Olivier; Whelan, James (Frontiers in Plant Science, 2012)
Throughout the life of a plant, the biogenesis and fine-tuning of energy organelles is essential both under normal growth and stress conditions. Communication from organelle to nucleus is essential to adapt gene regulation and protein synthesis specifically to the current needs of the plant. This organelle-to-nuclear communication is termed retrograde signalling and has been studied extensively over the last decades. In this study we have used large-scale gene expression data sets relating to perturbations of chloroplast and mitochondrial function to gain further insights into plant retrograde signalling and how mitochondrial and chloroplast retrograde pathways interact and differ. Twenty seven studies were included that assess transcript profiles in response to chemical inhibition, as well as genetic mutations of organellar proteins. The results show a highly significant overlap between gene expression changes triggered by chloroplast and mitochondrial perturbations. These overlapping gene expression changes appear to be common with general abiotic, biotic and nutrient stresses. However, retrograde signalling pathways are capable of distinguishing the source of the perturbation as indicated by a statistical overrepresentation of changes in genes encoding proteins of the affected organelle. Organelle-specific overrepresented functional categories among others relate to energy metabolism and protein synthesis. Our analysis also suggests that WRKY transcription factors play a coordinating role on the interface of both organellar signalling pathways. Global comparison of the expression profiles for each experiment revealed that the recently identified chloroplast retrograde pathway using phosphoadenosine phosphate (PAP) is possibly more related to mitochondrial than chloroplast perturbations. Furthermore, new marker genes have been identified that respond specifically to mitochondrial and/or chloroplast dysfunction.